Toxicity of White Turi Leaf Extract on Liver Function in Mice: Toksisitas Ekstrak Daun Turi Putih pada Fungsi Hati Mencit - Makrufah, Makrufah; Rohmah, Jamilatur (Indonesian Journal on Health Science and Medicine, 2025)
General background: Sesbania grandiflora (L.) Pers., widely known as white turi, is traditionally used as analgesic, laxative, and other medicinal purposes. Specific background: Despite its therapeutic benefits, the plant contains secondary metabolites, including triterpenoids and alkaloids, with potential hepatotoxic properties, particularly pyrrolizidine alkaloids. Knowledge gap: Previous studies have indicated general toxicity of turi extracts but limited evidence exists on its subacute hepatic toxicity measured through enzymatic markers in animal models. Aim: This study investigated the toxicity of white turi leaf extract on liver function by assessing SGOT and SGPT levels in mice (Mus musculus). Results: Laboratory experiments using a posttest-only control group design were conducted with multiple dosage levels. Statistical analysis with Kruskal-Wallis revealed no significant differences in SGOT (p = 0.896) and SGPT (p = 0.527) levels between treatment and control groups, while ANOVA showed no significant change in liver weight (p = 0.089). Novelty: This research provides the first evidence that ethanolic white turi leaf extract, within the tested doses and 14-day observation, does not induce measurable hepatic dysfunction in mice. Implications: The findings suggest relative safety of white turi extract at tested doses, supporting its potential traditional use while highlighting the importance of further chronic toxicity studies. Highlights : White turi leaf extract showed no hepatotoxic effect in mice. SGOT-SGPT levels and liver weight remained within normal range. Supports safe traditional use but requires chronic toxicity evaluation. Keywords : Sesbania Grandiflora, White Turi Leaf, SGOT, SGPT, Hepatotoxicity